LncRNA LUCAT1 contributes to cell proliferation and migration in human pancreatic ductal adenocarcinoma via sponging miR‐539 - Yongjun Nai; Chao Pan; Xueteng Hu; Yong Ma (Cancer Medicine, 2020)
Abstract Pancreatic ductal adenocarcinoma is one of the most aggressive and dreadful malignancies worldwide. Long noncoding RNAs (lncRNAs) have emerged as vital regulators in the development of human malignancies and other disorders. This study aimed to characterize the role of lncRNA lung cancer‐associated transcript 1 (lncRNA LUCAT1), a novel cancer‐related lncRNA, in human PDAC. Here we initially analyzed the expression patterns of lncRNA LUCAT1 and evaluated its clinical significance. The qRT‐PCR analysis and in situ hybridization staining showed that lncRNA LUCAT1 expression was significantly increased in tumorous tissues compared with adjacent normal tissues. Additionally, we found that increased lncRNA LUCAT1 expression was linked to larger tumor size and lymphatic invasion. Consistently, lncRNA LUCAT1 was remarkably up‐regulated in PDAC cell lines. To better understand the biological role of lncRNA LUCAT1, we evaluated the effects of lncRNA LUCAT1 knockdown on PDAC cell proliferation, cell cycle progression, migration, and invasion using MTT assays, flow cytometry, Transwell migration, and invasion assays, respectively. Functional studies demonstrated that lncRNA LUCAT1 knockdown dramatically suppressed PDAC cell proliferation, induced cell cycle arrest and inhibited cell migration and invasion. Tumor xenograft in vivo assays displayed that lncRNA LUCAT1 inhibited tumorigenecity of PDAC cells. Mechanistic studies uncovered that lncRNA LUCAT1 acted as a molecular sponge of miR‐539 and that miR‐539 mediated the effects of lncRNA LUCAT1 on PDAC cell proliferation, cell cycle progression, and motility. Collectively, our findings may offer some novel insights into understanding lncRNA LUCAT1 in PDAC.